Nonformal institutional interaction in a conversation club: Conversation partners' questions. Issue 3 (13th September 2015) - Hauser, Eric
Abstract : The data analyzed in this paper come from audio-recorded interaction among first and second language speakers of English at a conversation club sponsored by an English language school. As the analysis shows, the interaction in the conversation club can be understood as a type of non-formal institutional interaction. The analysis focuses on the questions asked by the first language speakers, or conversation partners. In particular, it focuses on the questioning styles of serial-questioning and pivoting. In addition, the conversation partners tend to assume a discourse identity as primary participant within the participation framework, a discourse identity that they work to maintain and, when necessary, re-establish. As non-formal institutional interaction, it does not involve turn pre-allocation or restrictions on the type of turn that participants may take. It is, though, oriented toward the fulfilment of institutionally relevant goals.